Information System Web-Based HSSE Performance In PT.XYZ - Irhandi, Irhandi; Coyanda, John; Saluza , Imelda (Journal of Computer Networks, Architecture and High Performance Computing, 2024)
Information Technology systems are developing very quickly and are a challenge for all types of industries. Data management of a company is very important in this digital 4.0 era. This system aims to help computerized data and information management is expected to reduce the risk of human error factors. The method begins with analyzing needs using the discussion method, translating data into UML (Unified Modeling Language) diagrams and implementing systems using web-based applications by taking data at PT XYZ, Department of Health, Safety, Security, Environment in processing HSSE Performance data which still uses semi-conventional applications and redundancies, so that it will produce an Information System that can make it easier for Company Management to Monitor the Achievement of HSSE Department Performance Targets which are presented visually in the form of a Dashboard. The design of the information system uses a prototype method that can be added or reduced according to the development process that can be adjusted to the needs of the company. This web-based application designs an HSSE Performance Information System to support operational data management in the company. The information system to be designed is the HSSE Performance information system in the HSSE Department, providing information results that can be used by leaders and management in making decisions.